The Relationship between Students’ Spiritual and Emotional Intelligence with Subjects Learning Outcomes - Muhajir Musa; Zulkifli Zulkifli; Devin Mahendika; Arifin Arifin; Ellyzabeth Sukmawati (Journal on Education, 2023)
The purpose of this study is to ascertain how student learning outcomes and emotional and spiritual intelligence are related. The quantitative approach with correlational study is the methodology employed. Techniques for gathering data in the form of surveys with questionnaires and measures of learning outcomes in the form of midterm exams (PTS). Assessing students' emotional and spiritual intelligence is done using questionnaires. This study used a simple random sampling method to select 106 students as its sample. The study's findings indicate a favorable correlation between emotional intelligence and student learning outcomes, a favorable correlation between emotional intelligence and spiritual intelligence, and a favorable correlation between emotional intelligence and spiritual intelligence and student learning outcomes.